-19=-3m-3m

Simple and best practice solution for -19=-3m-3m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19=-3m-3m equation:


Simplifying
-19 = -3m + -3m

Combine like terms: -3m + -3m = -6m
-19 = -6m

Solving
-19 = -6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '6m' to each side of the equation.
-19 + 6m = -6m + 6m

Combine like terms: -6m + 6m = 0
-19 + 6m = 0

Add '19' to each side of the equation.
-19 + 19 + 6m = 0 + 19

Combine like terms: -19 + 19 = 0
0 + 6m = 0 + 19
6m = 0 + 19

Combine like terms: 0 + 19 = 19
6m = 19

Divide each side by '6'.
m = 3.166666667

Simplifying
m = 3.166666667

See similar equations:

| Pxq=8x-3mpxs | | 5x-6=2+5x | | t=(c+b)x | | 4b-7b=-33 | | 4(5-x)6x=24 | | 4b-7b=33 | | abs(5x-10)=-25 | | (4y-10)=(2y+10) | | 5=8-(2)x | | 36x-11x=-100 | | 2(v-2)=5v+5-3(-5v-2) | | ln(x)=0.50 | | T(7t-9)=0 | | (3+4i)(5+2i)= | | 15X+4=-6x+5 | | 36=-7w+4(w+3) | | 2x=(12-30) | | f(x)=ln(3-t) | | ((x^4y^3)^1/3(x^2y^2)^2-3)/x^1/3y^1/3 | | 80=25x+25x | | -5x/9=-35 | | -5x/9=35 | | tanx+5=0 | | p=a-pxt | | y-9.1=0 | | 9.2x+7.1y-9.1=0 | | 14/9=-2v | | d/dx(1/e^nx) | | 8.6x+1.7y+7.3=0 | | -n/e^nx | | 28=-4/3x | | v+30=6v-5(1+8v) |

Equations solver categories